2010
DOI: 10.1111/j.1471-0307.2009.00548.x
|View full text |Cite
|
Sign up to set email alerts
|

Identifcation of yeasts from raw milk and selection for some specific antioxidant properties

Abstract: Eleven different species of yeasts isolated from raw milk, such as Issatchenkia orientalis, Pichia fermentans, Rhodotorula mucilaginosa and Yarrowia lipolytica were identified using an integrated approach, including phenotypic and genotypic methods and the API 20C AUX system. Eleven selected strains which tolerated low pH levels, gastric juice and bile salt were further analysed for the presence of functional traits useful for probiotic application as antioxidants. The ability to scavenge DPPH (2, 2-diphenyl-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 31 publications
7
32
0
2
Order By: Relevance
“…Both are urease positive (Table 1, Figure 1), which matches Chen et al (2010) for the urea hydrolysis test. Beckenkamp (1997), when working with pasteurized fruit pulp samples, also identified the genera Rhodotorula & Trichosporon, while Sancho et al (2000) identified R. mucilaginosa in pear pulp.…”
Section: Yeast Identificationsupporting
confidence: 67%
See 1 more Smart Citation
“…Both are urease positive (Table 1, Figure 1), which matches Chen et al (2010) for the urea hydrolysis test. Beckenkamp (1997), when working with pasteurized fruit pulp samples, also identified the genera Rhodotorula & Trichosporon, while Sancho et al (2000) identified R. mucilaginosa in pear pulp.…”
Section: Yeast Identificationsupporting
confidence: 67%
“…The downside of these techniques is the effort to extract and purify the DNA. On the other hand, a simple method based on the assimilative ability of substrates known as API 20C AUX has been widely used to identify yeasts (Silva & Candido, 2005;Chen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A test with cycloheximide showed that G. geotrichum was resistant to urea, but it was not resistant to cadaverine. Furthermore, no growth of G. geotrichum was detected on cellobiose, maltose, mellobiose, raffinose, mannitol, erythritol and α-methyl glucoside (Chen et al, 2010).…”
Section: Morphology Growth and Biochemical Propertiesmentioning
confidence: 94%
“…The G. geotrichum mould is able to grow at 3 to 11 pH, but the optimal is 5-7 pH (Skóra et al, 2009). Chen et al (2010) examined the yeast and moulds obtained from raw milk. Selected G. geotrichum isolates were able to grow on glucose and galactose, but could not ferment glucose and assimilate nitrate.…”
Section: Morphology Growth and Biochemical Propertiesmentioning
confidence: 99%
“…Similar results were also observed by Bautista-Gallego et al (2011) and Hernández et al (2007), in most yeasts isolated during fermentation of table olives. The ability of the yeast to produce this enzyme can be of great interest, since it is linked to the antioxidant capacity (Chen et al, 2010). In relation to lipase, C. tropicalis 3A, C. boidinii 32A and G. ressii 33A did not show any activity, while P. manshurica 2A and S. cerevisiae 15A and 15B showed high activity.…”
Section: Enzymatic Activitymentioning
confidence: 99%